Traditional Dietary Habits of Muslims: A Study Based on Ikkirigollawa Village of Anuradhapura District - Aroosiya Banu, M.S. (University of Sri Jayewardenepura, Sri Lanka, 2024)
The food practices and associated customs are basis in building the sense of community and thereby forming social identity. This study is designed as a descriptive study with the main objective of finding the traditional dietary habits of Ikkirigollawa village Muslims. The research has been carried out by simple random sampling procedure and 150 families were selected out of 1500. The data were collected and analyzed qualitatively as primary and secondary data. The traditional dietary habits of Muslims, the ingredients of food, types of food, superstition related to food customs and food customs during religious events were researched. In the findings of the study, the Muslims partially follow the dietary habits of the Sinhalese and Arab Muslims. It is significant that this village of Muslims are following to use the raw ingredients of food which are available in their environment and their traditional food system. These villagers also have the ability to choose food and cooking methods that are suitable for seasons and disease conditions. They also traditionally have the technical ability to preserve foods using food preservation techniques. Religious beliefs are given priority in their food habits. It is remarkable that the Ikkirigollawa village Muslims have traditional healthy dietary habits which is limited by religious aspects and still they are following them.
Keywords: Traditional Food; Muslims; Superstition; Village